2019
DOI: 10.1007/s12520-019-00804-9
|View full text |Cite
|
Sign up to set email alerts
|

Diet, cuisine and consumption practices of the first farmers in the southeastern Baltic

Abstract: With the arrival of the Early Neolithic Globular Amphora and Corded Ware cultures into the southeastern Baltic, ca. 2900/2800–2400 cal BC, a new type of economy was introduced, animal husbandry. However, the degree to which this transformed the subsistence economy is unknown. Here, we conducted organic residue analyses of 64 ceramic vessels to identify their contents. The vessels were sampled from 10 Lithuanian archaeological sites dating across the Subneolithic-Neolithic transition to the Early Bronze Age (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 55 publications
2
27
0
4
Order By: Relevance
“…Further information relating to their biological source was gained by measuring their carbon isotope values (Gas Chromatography-Combustion-Isotope Ratio Mass Spectrometry, GC-C-IRMS). This approach has been widely applied to European Neolithic pottery [22][23][24][25][26][27][28][29], and is increasingly being applied to hunter-gatherer pottery throughout the circum-Baltic region [22,[30][31][32]. Here, we report the outcome of organic residue analysis undertaken on 416 new royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Introductionmentioning
confidence: 99%
“…Further information relating to their biological source was gained by measuring their carbon isotope values (Gas Chromatography-Combustion-Isotope Ratio Mass Spectrometry, GC-C-IRMS). This approach has been widely applied to European Neolithic pottery [22][23][24][25][26][27][28][29], and is increasingly being applied to hunter-gatherer pottery throughout the circum-Baltic region [22,[30][31][32]. Here, we report the outcome of organic residue analysis undertaken on 416 new royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas during the Neolithic, farming seems to have replaced marine fishing in some Atlantic European coastal sites (e.g. Richards et al 2003), there is varied evidence available elsewhere, even if it is not highlighted by isotopic data (Robson et al 2019). In the Paris Basin, 4 As the different food sources are not known, the authors chose to not apply any mixing model to quantify proportions based on hypothetic food items.…”
Section: Food Economymentioning
confidence: 99%
“…Several studies have shown a correspondence between the bulk δ 13 C values of carbonized residues and absorbed lipids, where the combination of analyses have provided complementary data to support conclusions regarding vessel use [35][36][37][38][39][40] . For example, both bulk δ 13 C values and individual fatty acid δ 13 C values can discriminate between habitats, such as terrestrial versus aquatic species (and further refinement between freshwater, marine, and anadromous species), since marine species are 13 C enriched [35][36][37][38][39]41 .…”
mentioning
confidence: 98%